CHALLENGES FACED BY GRADUATE PROFESSIONALS WHEN CHOOSING A POSTGRADUATE COURSE - Renan Giménez Carreras, Giovanni; Alfredo Chaparro Brítez, Luis; Elisa Martínez de Vera, Norma; Rosa Trinidad de Ferreira, Nidia (Revista Gênero e Interdisciplinaridade, 2023)
The present work is a study about the difficulties that graduated professionals have in choosing a postgraduate course. The main objective of the work is to investigate what are the greatest difficulties that university professionals have in seeking information about the institutions and postgraduate courses that exist within the country as well as abroad. The research is carried out at the Universidad Privada del Este, Ciudad del Este headquarters, where people were randomly selected to respond to the surveys, finding an excellent willingness from everyone for the consultations. With the results obtained, the conclusion is reached of the great interest they have in taking a postgraduate course and the lack of clear and precise information regarding the courses offered.